SYNTHESIS OF NANOCOMPOSITE FIBERS BASED ON ROCK PITCH AND NANOIRON BY ELECTROSPINNING - Yermagambet Bolat Toleukhanuly; Kazankapova Maira Kuttybaevna; Kassenova Zhanar Muratbekovna; Nauryzbaeva Asemay Turlangyzy (Academic Journal of Physical and Chemical Sciences, 2020)
The article presents experiments on the production of nanocomposite fibers based on the Shubarkol coal tar pitch and nano-iron by the method of electrospinning in a laboratory setup. The elemental composition was determined and the surface morphology of the test sample was studied. As a result of energy dispersive X-ray spectroscopy and SEM microscopy, the elemental composition was determined: C-92.14%, O-6.16%, Al-0.30%, Si-0.26%, P-0.07%, S -0.20%, Cl -0.40%, Fe-0.47% and the diameter of the carbon nanofiber, which ranged from 94.2 nm to 800.0 nm. The results of IR spectroscopy showed an increase in the intensity of the peaks in the region of 2920-2850 cm-1 and the appearance of a signal at 2359 cm-1, which is explained by the breaking of several chemical bonds in the sample structure and the formation of a composite with nano-iron.